PROCESS TYPES IN EFL LEARNERS’ NARRATIVE TEXT: A PORTRAIT ON LINGUISTICS AND GENDER CONNECTIONS - Aldha Williyan; Lala Bumela (IAIN Syekh Nurjati Cirebon, 2016)
Abstract: This present study explores the female and male EFL learners’ process types in their narrative text to connect the linguistics and gender. According to Bank (2007, 3-4) school help to shape the sex-role socialization theorists: that is, the theory which focuses on how people learn the role of male and female in the society. Thus, this study is intended to: 1) find out the differences between both female and male in term of process types in narrative text, 2) find out the relation between gender of writers and the choice of process types in writing narrative text. This study shows that female EFL learner uses eleven process types; material (37%), attributive intensive (22,6%), mental affection (7,5%), behavioral (7,5%), identifying intensive (6,1%), mental perceptive (5,4%), verbal (4,8%), attributive possessive (4,1%), mental cognition (2,7%), causative (1,3%), and existential process (0,7%). In contrast, the male respondent tends to use and produce only nine kinds of process types in his narrative text. Those process types are the material (47%), Verbal (13,3%), behavioral (12,2%), attributive intensive (8,1%), identifying intensive (5,8%), mental cognition (4,6%), mental perceptive (4%), attributive possessive (3,4%), mental affection processes (1,1%). Key words: process types, gender,Male EFL learner, Female EFL learner